Beneficial Effect of the Traditional Chinese Drug Shu-Xue-Tong on Recovery of Spinal Cord Injury in the Rat. (8th September 2010) - Jia, Li-Yun; Yao, An-Hui; Kuang, Fang; Zhang, Yu-Kai; Shen, Xue-Feng; Ju, Gong
Abstract : Shu-Xue-Tong (SXT) is a traditional Chinese drug widely used to ameliorate stagnation of blood flow, such as brain or myocardial infarction. Whether SXT may have therapeutic value for spinal cord injury (SCI), during which ischemia plays an important role in its pathology, remains to be elucidated. We hypothesized that SXT may promote SCI healing by improving spinal cord blood flow (SCBF), and a study was thus designed to explore this possibility. Twenty-five male Sprague-Dawley rats were used. SCI was induced by compression, and SXT was administrated 24 h postinjury for 14 successive days. The effects of SXT were assessed by means of laser-Doppler flowmetry, motor functional analysis (open-field walking and footprint analysis), and histological analysis (hematoxylin-eosin and thionin staining and NeuN immunohistochemistry). SXT significantly promoted SCBF of the contused spinal cord and enhanced the recovery of motor function. Histological analysis indicated that the lesion size was reduced, the pathological changes were ameliorated, and more neurons were preserved. Based on these results we conclude that SXT can effectively improve SCI.